2019
DOI: 10.1785/0120190055
|View full text |Cite
|
Sign up to set email alerts
|

An Earthquake Nest in Cascadia

Abstract: We investigate an isolated cluster of temporally persistent, intraslab earthquakes (ML<3.2) at >60  km depth below the Georgia Strait in southern British Columbia that is unique in Cascadia and meets the criteria for identification as an earthquake nest. A total of 129 relocated hypocenters define two northwest‐dipping structures in the subducting Juan de Fuca mantle within an ∼30×10×10  km3 volume. Focal mechanisms for 15 events represent a mix of strike‐slip and reverse faulting, and a stress regime of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…This suggests that there is a greater occurrence of faulting within the PW, which potentially is the primary factor behind the observed decrease in density compared to the surrounding oceanic crust. The findings of this paper—PWs have lower densities than the surrounding crust—are also consistent with several studies relating the PWs of the JdF plate to observed seismicity clusters (Han et al., 2018; Merrill & Bostock, 2019; Nedimović et al., 2009), thus confirming crustal weaknesses along these structures. PWs around the world also show similar signatures of enhanced crustal fracturing and require lower densities during gravity modeling (Peirce et al., 2001; Wiedicke & Collier, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that there is a greater occurrence of faulting within the PW, which potentially is the primary factor behind the observed decrease in density compared to the surrounding oceanic crust. The findings of this paper—PWs have lower densities than the surrounding crust—are also consistent with several studies relating the PWs of the JdF plate to observed seismicity clusters (Han et al., 2018; Merrill & Bostock, 2019; Nedimović et al., 2009), thus confirming crustal weaknesses along these structures. PWs around the world also show similar signatures of enhanced crustal fracturing and require lower densities during gravity modeling (Peirce et al., 2001; Wiedicke & Collier, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Another example of an isolated seismicity cluster in space and time was recently documented in northern Cascadia. Merrill and Bostock (2019) identified an earthquake nest located in the Juan de Fuca mantle at depths greater than 60 km and concentrated in a 30 × 10 × 10 km 3 volume. Generally, nests are classified as intraslab intermediate depth seismicity that persists for decades (Prieto et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of similar earthquake clusters elsewhere on the Island suggests that Wrangellia, the terrane that comprises most of Vancouver Island, is a relatively coherent crustal block in which brittle deformation is primarily manifest in larger, isolated events like those in 1918, 1946, and 1957(Rogers, 1983Cassidy et al, 1988). Notable earthquake concentrations adjacent to Vancouver Island include the Texada intraplate earthquake nest (Merrill & Bostock, 2019), the San Juan Island cluster (Balfour et al, 2012), seismicity in the upper Fraser Valley (Balfour et al, 2012), and shallow events within the Georgia Strait (Cassidy et al, 2000). Whereas those earthquake sequences have been previously documented, our study affords structural constraints for several minor earthquake clusters on the west coast of Vancouver Island near the town of Ucluelet.…”
Section: Vancouver Islandmentioning
confidence: 99%